(3fZHI GdHjGf aj JaSjQ GdbQBfs - (3TgGH GdOjf YeQ Hf eMehO GdSgQhQOj,J (B632 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ChOY cJGHg GdYRjR HhGdZ GdMce JaSjQ aGJMI GdcJGH bhdg JYGdi HSe Gddg GdQMef GdQMje cCfg bGd HOCJ HSe Gddg Ch CHOC HSe Gddg hMPaJ GdCda ef HSe Gddg s
(3BNQgG (B:s
(3jfJgi HJaSjQ ShQI GdfGS s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1965s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs